Tardigrades of Sweden; an updated check-list - Guidetti, Roberto; Jönsson, K. Ingemar; Kristensen, Reinhardt Møbjerg (Zootaxa, 2015)
Tardigrades occur worldwide and in a variety of ecosystems and habitats representing an important component of the micrometazoan biodiversity. Several studies documenting the occurrence of tardigrades in Sweden have been published since the first reports in early 1900, but no comprehensive summary of these studies have been published. We compiled the available information on recorded tardigrades from Sweden, using material from published studies and museum and university collections. In total, our review document 101 species of tardigrades that have been recorded from Sweden (an updated checklist of tardigrades from Sweden will be available online), of which 14 species are new records for the country. The highest number of species was recorded in the northernmost province of Lappland and the more southern provinces of Uppland and Skåne, while much lower species numbers are reported from the middle part of Sweden. This pattern probably represents biased sampling activities of biologists rather than real differences in biodiversity of tardigrades. In view of the few studies that have been made on tardigrade biodiversity in Sweden, the relatively high number of tardigrade species recorded, representing almost a tenth of the species recorded worldwide, indicates that many more species remain to be found. In this respect, more studies of the marine ecosystems along the Swedish west coast and the long Baltic Sea coastline would be of particular interest.